1978
DOI: 10.1037/0735-7028.9.4.692
|View full text |Cite
|
Sign up to set email alerts
|

The public and the help-giving professions in Australia.

Abstract: AILEEN FLVNN is a social worker in a general medical hospital. KATHRYN CAVE, GREGORY HODGSON, MARK PROUATT, AND WILLIAM SULTMANN are undergraduate psychology students. JAMES M. GARDNER if a Fellow of the American Association on Mental Deficiency and of the Australian Psychological Society. He is a former editorial board member of Professional Psychology and has been a consulting editor of several other journals. He is currently a professor in and Head of the Division of Applied Psychology, University of the Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
13
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
4
13
0
Order By: Relevance
“…In Australia, interest in the area has generally focussed on comparing psychologists with other established professionals (Small & Gault, 1975) or health professionals in particular (Donovan, 1985; Sharpley. 1986; Wilkinson et al, 1978). Recent reviews of community attitudes towards psychologists in Australia (Sharpley, 1986) and in the USA (Webb & Speer, 1986; Wood, Jones, & Benjamin, 1986) concluded that divergent methodologies and foci made it difficult to arrive at an accurate conclusion as to the public's knowledge and attitudes.…”
mentioning
confidence: 99%
“…In Australia, interest in the area has generally focussed on comparing psychologists with other established professionals (Small & Gault, 1975) or health professionals in particular (Donovan, 1985; Sharpley. 1986; Wilkinson et al, 1978). Recent reviews of community attitudes towards psychologists in Australia (Sharpley, 1986) and in the USA (Webb & Speer, 1986; Wood, Jones, & Benjamin, 1986) concluded that divergent methodologies and foci made it difficult to arrive at an accurate conclusion as to the public's knowledge and attitudes.…”
mentioning
confidence: 99%
“…This discrepancy may suggest that participants are confusing counselling psychologists with counsellors and clinical psychologists with psychiatrists and that, when given the opportunity to provide a more elaborative response, may be drawing on well‐established stereotypes that underlie the commonly encountered terms of “counselling” and “psychiatry” (Dempsey, 2007). Indeed, the roles and professional functions of psychologists and psychiatrists have been confused for many years (Small & Gault, 1975; Tallent & Reiss, 1959; Webb & Speer, 1986; Wilkinson et al., 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Where earlier research has shown a relative lack of understanding (Guest, 1948; Small & Gault, 1975; Thumin & Zebelman, 1967; Wilkinson et al., 1978) more recent studies have demonstrated a shift towards greater knowledge of MHPs (Agnew, 2003; Sharpley et al., 2004; Wood et al., 1986). This may suggest that, in contrast to earlier suggestions (Hopson & Cunningham, 1995; Sharpley, 1986), psychologists are playing an increasingly relevant role in people's lives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations